Hubungan Waktu Tunggu Dan Length Of Stay (LOS) Dengan Kepuasan Pasien - Muhammad Habibi; Juando Juando; Chrismis Novalinda Ginting (Universitas Haji Sumatera Utara, 2023)
The Emergency Department is one of the most important units of a hospital that serves as a place to handle emergencies at the main gate. Emergency room services are a type of quality care in a timely manner. Triage is a type of assessment that is precise, fast, and responsive with the time possible in utilizing human resources, facilities, and equipment efficiently. In the Emergency Department length of stay and waiting time can see clinical performance and density levels. Length of stay in the emergency department can see clinical workload and overcrowding levels. This study uses correlation analytic research procedures using a cross-sectional approach which aims to determine the relationship between waiting for time and length of stay and patient satisfaction in the Emergency Department of RSU. Royal Prima Marelan. The population in this study amounted to 72 respondents. The sampling technique was saturated sampling, so the sample was 72 people. The results of the study obtained 52 respondents (72.3%) were satisfied with the waiting time and Length of Stay in the Emergency Room of the Royal Prima Marelan Hospital. The results of the Chi-Square statistical test obtained p-value = 0,157 (p <0.05) so that the Alternative Hypothesis (Ha) can be accepted which means that there is no relationship between waiting for time and Length of Stay and satisfaction of emergency room patients.